Dynamic contrast‐enhanced MRI in mice at high field: Estimation of the arterial input function can be achieved by phase imaging. Issue 2 (25th February 2013) - Fruytier, A.‐C.; Magat, J.; Colliez, F.; Jordan, B.; Cron, G.; Gallez, B.
<x xml:space="preserve">Abstract</x> Purpose Quantitative dynamic contrast‐enhanced MRI requires an accurate arterial input function (AIF). At high field, increased susceptibility effects and decreased longitudinal relaxivity of contrast agents lead to predominant T2* effects in blood vessels, producing a dip in signal during passage of the contrast agent bolus. This study determined phase‐derived AIFs in mice at 11.7 T. Methods AIFs were measured in aorta/vena cava for five FBV/N mice and in iliac arteries/veins for five NMRI mice with a fast low angle shot sequence, simultaneously with tumor imaging (temporal resolution: 1.19 s). Gadoterate was injected into the tail vein as a bolus (0.286 mmol Gd/kg). An in vitro study was also performed to calculate the relationship between ΔΦ and gadolinium concentration. Results The phantom system confirmed the linear relationship between measured ΔΦ and gadolinium concentration. In vivo, a dip in arterial magnitude signal made it impossible to quantify the AIF. With phase imaging, a clear quantifiable bolus peak was obtained; peak measured concentration in plasma was 4.9 ± 0.9 mM for FBV/N mice and 8.0 ± 0.6 mM for NMRI mice, close to the expected concentration of 6.8 mM. Conclusion Phase imaging seems to be an appropriate means to measure the AIF of mice at high field. Magn Reson Med 71:544–550, 2014. © 2013 Wiley Periodicals, Inc.